A study on reaction kinetics and development of silicide coatings on Nb–1Zr–0.1C alloy by molten salt technique. Issue 101 (19th October 2016) - Tyagi, M.; Vishwanadh, B.; Bhattacharyya, K.; Ghosh, S. K.; Tewari, R.
Abstract : In this study a molten salt technique has been used to produce silicide coating on Nb–1Zr–0.1C alloy using a NaCl–KCl–NaF–Na2 SiF6 –Si melt. Abstract : In this study a molten salt technique has been used to produce silicide coating on Nb–1Zr–0.1C alloy using a NaCl–KCl–NaF–Na2 SiF6 –Si melt. Molten baths having different concentrations of Si in the metallic state produced silicide coating whereas those molten baths which were devoid of metallic Si could not produce any coating. Structural and chemical characterization of the coated samples by scanning electron microscopy (SEM) and X-ray diffraction (XRD) have shown that the uniform coating had NbSi2 as a major phase. Depending upon the composition of the salts, post experiment examination by X-ray photoelectron spectroscopy (XPS) technique and ion chromatography revealed the presence of varying relative concentrations of various states of silicon, F − and the etched Nb. Based on the analysis of these results it was elucidated that the presence of Si 2+ is a prerequisite for silicide coating on the Nb alloy. A mechanism of silicide coating formation on Nb alloy by the molten salt technique has been proposed in the present study.